PENERAPAN MEDIA KARTU UNTUK KETERAMPILAN MENULIS BAHASA JERMAN KELAS X BAHASA SMA NEGERI 1 DRIYOREJO GRESIK - Saputri, Ajeng Apriliko; Wahyuningsih, Fahmi (LATERNE, 2022)
Writing skills are one of the language skills that need to be mastered in learning foreign languages, in addition to listening skills, speaking skills and reading skills. Based on the results of an interview with a German teacher at SMAN I Driyorejo Gresik, information was obtained from many students who still have difficulty in writing simple sentences in German. It is necessary to find a solution. One of them is the use of card media. The card media used for application in this study was adapted from the UNO card game, where the colors and numbers contained in the UNO card were removed and then replaced with vocabulary which contained vocabulary in the form of nouns and verbs. The formulation of the problem in this study is "what is the process of applying card media in German writing skills in class X Language students of SMA Negeri 1 Driyorejo Gresik?". While the purpose of this study is to find out the process of applying card media in learning German writing skills for students - students of class X Language SMA Negeri 1 Driyorejo Gresik. In connection with this purpose, this research is a descriptive research. The data sources carried out in the following research were obtained through class X students of SMA Negeri 1 Driyorejo Gresik. The data in the following study is data on the process of applying card media. The data from the writing test of class X students of driyorejo Gresik State High School in German with the theme Schule with card media is to support data. The results of this study show that the card media has been applied well and received a good response from the students during the writing skills learning activity by applying cards. From the results of observations, it shows that students are more active during the learning process by applying using card media. Through the medium of the card, students become enthusiastic about learning and there is motivation throughout the teaching activity. Using this card media, students can cooperate in a group, give each other help in learning German, increase students' creativity, and make boring and monotonous learning situations more enjoyable and exciting. Students' German writing skills are improving and student learning outcomes are better than ever.